2017
DOI: 10.1111/ejn.13698
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range cortical dynamics: a perspective from the mouse sensorimotor whisker system

Abstract: In the mammalian neocortex, the capacity to dynamically route and coordinate the exchange of information between areas is a critical feature of cognitive function, enabling processes such as higher-level sensory processing and sensorimotor integration. Despite the importance attributed to long-range connections between cortical areas, their exact operations and role in cortical function remain an open question. In recent years, progress has been made in understanding long-range cortical circuits through work f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 134 publications
0
17
0
Order By: Relevance
“…This explains the behavioral effect of S2 inactivation during the late delay, but not the test, period. Recent studies investigating S1 and S2 during tactile detection or discrimination tasks have demonstrated that choice-related activity emerges through learning (Chen et al, 2015;Yamashita and Petersen, 2016) from an inter-areal loop in which choicerelated activity in S1 is inherited from S2 (Chen et al, 2016;Kwon et al, 2016;Ni and Chen, 2017;Yang et al, 2016). We propose that choice activity described in prior tasks reflects a stimulus-outcome association rather than the decision signal driving behavior.…”
Section: Discussionmentioning
confidence: 79%
“…This explains the behavioral effect of S2 inactivation during the late delay, but not the test, period. Recent studies investigating S1 and S2 during tactile detection or discrimination tasks have demonstrated that choice-related activity emerges through learning (Chen et al, 2015;Yamashita and Petersen, 2016) from an inter-areal loop in which choicerelated activity in S1 is inherited from S2 (Chen et al, 2016;Kwon et al, 2016;Ni and Chen, 2017;Yang et al, 2016). We propose that choice activity described in prior tasks reflects a stimulus-outcome association rather than the decision signal driving behavior.…”
Section: Discussionmentioning
confidence: 79%
“…S1 barrel cortex has long been recognized as a key locus for whisker-guided behaviors. While S1 is densely interconnected with many cortical and subcortical areas, including thalamus, higher-order sensory, motor, and association cortices [4547], the detailed circuitry and behavioral roles of these pathways are just beginning to be understood [65, 66]. For example, S1 interactions with M1 and S2 are now recognized as important for detection of sensory stimuli, behavioral performance, and learning [5356, 58, 67, 68].…”
Section: Discussionmentioning
confidence: 99%
“…Because the temporal order of early BOLD responses reflected information flow among longrange somatosensory regions, our next question was whether the neural activation sequence could be identified by the layerdependent onset times. In S1FL, neurons in L4 are known to respond first during forepaw stimulation due to TC inputs from VPL (33,34), whereas neurons in L2/3 respond first during optogenetic stimulation in M1 due to CC inputs from M1 (33,35). To measure spatiotemporal changes at a laminar resolution, we flattened the cortical section containing S1FL and MI (Fig.…”
Section: Of 9 | Pnasmentioning
confidence: 99%